2019
DOI: 10.1097/brs.0000000000003121
|View full text |Cite
|
Sign up to set email alerts
|

In Degenerative Spondylolisthesis, Unilateral Laminotomy for Bilateral Decompression Leads to Less Reoperations at 5 Years When Compared to Posterior Decompression With Instrumented Fusion

Abstract: Study Design. Multicenter retrospective cohort study. Objective. The aim of this study was to compare reoperation rates at 5-year follow-up of unilateral laminotomy for bilateral decompression (ULBD) versus posterior decompression with instrumented fusion (Fusion) for patients with low-grade degenerative spondylolisthesis (DS) with lumbar spinal stenosis (LSS) in a multicenter database. Summary of Background Data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…However, there is a lack of clinical evidence to com rm its safety and e cacy comparing PEID to TLIF. The current study shows that ULBD technique is a viable option for patients with moderate and severe LSS 14 . Absence of muscle dissection with the endoscope and instruments over the lamina and preservation of the soft tissue structures, could alleviate the muscle atrophy and spinal instability 15 .…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…However, there is a lack of clinical evidence to com rm its safety and e cacy comparing PEID to TLIF. The current study shows that ULBD technique is a viable option for patients with moderate and severe LSS 14 . Absence of muscle dissection with the endoscope and instruments over the lamina and preservation of the soft tissue structures, could alleviate the muscle atrophy and spinal instability 15 .…”
Section: Discussionmentioning
confidence: 65%
“…PEID was reported to treat several degenerative lumbar disease, such as degenerative scoliosis and spondylolisthesis, lumbar stenosis, and thoracic disc herniations 14,22,23 . Previous reports have already demonstrated that ULBD is a effective and safe approach to treat degenerative spondylolisthesis 10 .Several clinical study focused attentionon the clinical e cacy of ULBD for the treatment of severe lumbar stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar spinal stenosis (LSS) with degenerative spondylolisthesis is an important cause of low back pain (1). The optimal treatment for patients of LSS with degenerative spondylolisthesis remains uncertain (2,3). Surgery may be necessary to relieve the symptoms and improve function after failed conservative treatment in patients of LSS with degenerative spondylolisthesis (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Minimally invasive transforaminal lumbar interbody fusion (MI-TLIF) was firstly described by Foley et al and had been commonly performed to treat LSS with degenerative spondylolisthesis (10)(11)(12). Decompression alone was also used to treat LSS with degenerative spondylolisthesis to preserve the facet joints, paraspinal musculoligamentous structures, mitigate the risk of adjacent segment fusions after instrumented fusion, and to reduce the healthcare cost (2). Minimally invasive unilateral laminotomy bilateral decompression was performed to treat LSS with degenerative spondylolisthesis to minimize the injury to the paraspinal musculoligamentous structures (6).…”
Section: Introductionmentioning
confidence: 99%
“…Precisely identifying the The associate editor coordinating the review of this manuscript and approving it for publication was Cristian A. Linte. vertebral body, spinal canal and dural sac is helpful in diagnosing different types of LSS [2]. Surgeons usually use lumbar spinal CT images to distinguish between degenerative and developmental LSS because CT is better at imaging osseous and calcified tissues than MRI is [3].…”
Section: Introductionmentioning
confidence: 99%